Peningkatan Minat Belajar Siswa dalam Mengikuti Pembelajaran Seni Budaya Menggunakan Aplikasi Digital (Whatsapp, Youtube, Tiktok, Instagram) di SMKS Sunan Bonang - Isyuniandri, Dzaky; Sulianti, Ani; Bella, Shinta; Alam, Mihbub (Indo-MathEdu Intellectuals Journal, 2023)
The implementation of this research was caused by the low interest of students in learning cultural arts. The purpose of this study is to increase students' interest in participating in cultural arts learning using digital applications (WhatsApp, Youtube, Tiktok, Instagram). To determine whether there is an increase in student interest in learning using digital application media (WhatsApp, Youtube, Tiktok, Instagram), this study uses the type of Classroom Action Research. Data was collected using observations, field notes, and documentation. Data analysis is carried out descriptively on all data obtained. The results of the data analysis showed that there was a very significant increase in student interest in participating in Cultural Arts learning in the competence of Fine Arts and Dance from the first cycle which was only 46.6% which was classified as good, increasing to 83.3% in the second cycle. From the results of the data above, researchers determined that the success indicators of this study had been achieved well, even exceeding the achievement targets that had been set.